2008
DOI: 10.1111/j.1365-2702.2008.02388.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors related to incidence of eye disorders in Korean patients at intensive care units

Abstract: An evidence-based eye care protocol should be provided as routine care to prevent eye complication, especially in critically ill patients with mechanical ventilators, positive end expiratory pressure, sedatives or muscle relaxants and for patients whose mental status is decreased.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
26
2
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 12 publications
0
26
2
3
Order By: Relevance
“…Factors such as sedation, use of drug combinations, mechanical ventilation, prolonged admission time, low humidity, low temperature and lagophthalmia are examples of risk factors often present in ICU and thus favour a prevalence of more than 70% of patients with eye dryness up to five days of hospitalization (3) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Factors such as sedation, use of drug combinations, mechanical ventilation, prolonged admission time, low humidity, low temperature and lagophthalmia are examples of risk factors often present in ICU and thus favour a prevalence of more than 70% of patients with eye dryness up to five days of hospitalization (3) .…”
Section: Discussionmentioning
confidence: 99%
“…It presented 72.2% cases in Intensive Care Units, which shows a high incidence of the phenomenon in this sector (3) . The ICU are care sectors for patients who are more dependent on account of a serious or risky health condition.…”
Section: Introductionmentioning
confidence: 99%
“…5,10,34 In a Nigerian study with 56 patients, the MV (4.55 ± 2.97 vs 1.62 ± 1, 02 days) was statistically significant for the development of ocular surface changes, with a p <0,05. 1 Despite not having found a frequency equal to or greater than 50% for the risk factor hospitalization time, in 12 studies (44.44%) [3][4][5]8,16,31, this was identified as an important predictor for the development of ocular abnormalities in critically ill patients.…”
mentioning
confidence: 99%
“…1 In the Chinese study, which examined 2500 records, the average time found for the identification of alterations of the ocular surface was 6.8 days. 31 …”
mentioning
confidence: 99%
See 1 more Smart Citation